Foreign dollar balances and the international role of the dollar - Mikesell, Raymond Frech; Furth, Josef Herbert (New York : National Bureau of Economic Research; distributed by Columbia University Press, 1974)
The book focused on the origin, composition, and behavior of foreign dollar holdings, the present study sets forth an analytical framework for studying the interrelations among the several types of liquid dollar assets as determined by the behavior of the major categories of foreign portfolio holders.
includes index
usc 26/05/2017
Loans
Keywords: International liquidity; International finance; Balance of payments; Dollar, American